Competence Assessment Instruments in Perianesthesia Nursing Care: A Scoping Review of the Literature - Jeon Y; Lakanmaa RL; Meretoja R; Leino-Kilpi H (ELSEVIER SCIENCE INC, 2022)
Purpose: To identify competence assessment instruments in perianesthesia nursing care and to describe the validity and reliability of the instruments.Design: A scoping review in a systematic manner.Methods: A search in CINAHL, MEDLINE, and ERIC was carried out to identify empirical studies from 1994 to 2015. A narrative synthesis approach was undertaken to analyze the data.Findings: Nine competence assessment instruments in perianesthesia nursing care were identified. The instruments used three types of data collection methods: Self-report, observation, and written examinations. The most commonly reported validity method was content validity involving expert panels and reliability tests for internal consistency and inter-rater's consistency.Conclusions: Integrating more than one data collection method may give support to overcoming some of the limitations, such as lack of objectivity and misinterpretation of the assessment results. In an ever-changing environment, perianesthesia nursing competence requires constant reassessment from the perspective of content validity, scoring methods, and reliability.